(untitled) (Huellas, 2016)
The Platense Horticultural Belt has shown an economic, production and technological irrefutable and uninterrupted growth from its birth (1882) up to the present. Moreover, the speed and magnitude of the transformations in the last years would seem to correspond to causes that have not yet been clearly and / or fully identified or stated. In this sense, it is noteworthy that the considerations of the territory in the economic studies of recent years seek to elucidate the factors that explain the concentration processes of production and service activities in certain spaces, as well as those which lead certain locations to show greater dynamism and competitive capacity than others. Thus, the objectives posed in this work are to locate the approaches of economic agglomerates and to determine the externalities resulting from the agglomeration of horticultural companies in La Plata. A bibliographical classification of the different conceptualizations, characteristics and types of companies agglomerates was performed to this end. Afterwards, the existing interrelationships in La Plata’s agglomerate were identified and analyzed, as well as their emergent competitive advantages. It is concluded that the case of horticulture in La Plata shows an evolution that resembles that of other economic agglomerates, being the concept of Productive Local Systems the one that, at present, is best suited to describing and interpreting its dynamics.